2017
DOI: 10.1038/srep43576
|View full text |Cite
|
Sign up to set email alerts
|

(+)/(−)-Phaeocaulin A-D, four pairs of new enantiomeric germacrane-type sesquiterpenes from Curcuma phaeocaulis as natural nitric oxide inhibitors

Abstract: Germacrane-type sesquiterpenes, with a flexible 10-membered ring unit as the structural and conformational features, play a central role in the biosynthesis and synthesis of other sesquiterpenes. In this report, two pairs of new sesquiterpene alkaloids, (+)/(−)-phaeocaulin A [(+)-1/(−)-1] and B [(+)-2/(−)-2], and two pairs of new sesquiterpenes, (+)/(−)-phaeocaulin C [(+)-3/(−)-3] and D [(+)-4/(−)-4], along with one related known analog (5), were isolated from the rhizomes of Curcuma phaeocaulis. The absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…NO is biosynthesized endogenously from L-arginine, oxygen, and NADPH by various NOS enzymes, playing a role in a variety of biological processes [36]. To evaluate the inflammatory reactions, the levels of IL-10 (anti-inflammatory factor) and IL-6 (pro-inflammatory factor) in the renal tissue were also measured.…”
Section: Resultsmentioning
confidence: 99%
“…NO is biosynthesized endogenously from L-arginine, oxygen, and NADPH by various NOS enzymes, playing a role in a variety of biological processes [36]. To evaluate the inflammatory reactions, the levels of IL-10 (anti-inflammatory factor) and IL-6 (pro-inflammatory factor) in the renal tissue were also measured.…”
Section: Resultsmentioning
confidence: 99%
“…experimented with some isolated phytoconstituents from Curcuma phaeocaulis concerning their inhibitory effect on NO production and found that several compounds had moderate inhibitory effects on NO synthesis with the range of IC50 values of 17.34 to 30.02 µM. However, the mechanisms of action of these compounds remained unexplored [ 149 ]. The NO inhibitory effects of phacadinanes A–D, which are four cadinane-type sesquiterpenes isolated from C. phaeocaulis, were examined in LPS-activated macrophages and it was found that two of these compounds possessed strong inhibitory activities with IC50 values of 3.88±0.58 and 2.25±0.71 μM [ 150 ].…”
Section: Inhibition Of Nitric Oxide Productionmentioning
confidence: 99%
“…Qiu and coworkers reported four pairs of megastigmane-type norsesquiterpenoid enantiomers 315a/315b−317a/317b and 325a/325b from Eucommia ulmoides in 2017, while the racemic mixtures of 315 and 325, along with pure enantiomers 316b and 317b, had been previously reported [163]. Compounds 318a/318b and 319a/319b are two pairs of enantiomeric germacrane type sesquiterpenes from Curcuma phaeocaulis reported in 2017 [128]. Chai and colleagues discovered 320a/320b−324a/324b with a humulane framework and 329a/329b incorporating a rare 2,2,5,9-tetramethylbicyclo[6.3.0]-undecane skeleton from Syringa pinnatifolia [164].…”
Section: Sesquiterpenoidsmentioning
confidence: 95%
“…configs. by using modified Mother's method [83], and two pairs of germacrane-type sesquiterpenoid lactams 239 and 240 were obtained from Curcuma phaeocaulis by Qiu and colleagues [128]. Compounds 241a/241b and 242a/242b are flavonoid alkaloid enantiomers reported from Scutellaria moniliorrhiza in 2018 [129], while 243a/243b represent a pair of 9,10-dihydrophenanthrene alkaloid enantiomers from Bletilla striata [130].…”
Section: Other Alkaloidsmentioning
confidence: 99%